CRISPR-Cas13a-based detection method for avian influenza virus - Wu, Yuhan; Zhan, Jiaxing; Shan, Zhaomeng; Li, Yanbing; Liu, Yining; Li, Yan; Wang, Yixin; Liu, Zhe; Wen, Xuexia; Wang, Xiurong (Frontiers in Microbiology, 2023)
Avian influenza virus (AIV) causes huge losses to the global poultry industry and poses a threat to humans and other mammals. Fast, sensitive, and portable diagnostic methods are essential for efficient avian influenza control. Here, a clustered regularly interspaced short palindromic repeats (CRISPR)-Cas13a based platform was developed to detect AIV. This novel method was developed to specifically detect H1-H16 subtypes of AIV with fluorescence and lateral flow-based readouts and exhibited no cross-reactivity with Newcastle disease virus, avian infectious bronchitis virus, or infectious bursal disease virus. The limit of detection was determined to be 69 and 690 copies/μL using fluorescence and lateral flow as readouts, respectively. The developed assay exhibited 100% consistency with quantitative real-time polymerase chain reaction in detecting clinical samples. The heating of unextracted diagnostic samples to obliterate nuclease treatment was introduced to detect viral RNA without nucleic acid extraction. Single-step optimization was used to perform reverse transcription, recombinase polymerase amplification, and CRISPR-Cas13a detection in a tube. These advances resulted in an optimized assay that could specifically detect AIV with simplified procedures and reduced contamination risk, highlighting the potential to be used in point-of-care testing.